The impact of climate change and green financing on bank stability in Malaysia / Mohd Razuan Abd Hishamuddin ... [et al.] - Abd Hishamuddin, Mohd Razuan; Bujang, Imbarine; Rimin, Flicia; Said, Jamaliah; Nainggolan, Dwi Astuti Rosmianingrum (Universiti Teknologi MARA Selangor, 2023)
Banking stability is paramount for economic growth. A sound financial intermediation process leads to the creation of loans from depositors to borrowers, guaranteeing the nation's development. However, banking businesses through credit facilities could severely cause environmental degradation and economic development. The non-green financing facilities have influenced climate change to rise and be uncontrollable, leading to inconclusive and unclear findings among scholars. The aim of this paper is to examine the impact of climate change and green financing on bank stability in Malaysia. The sample consists of eight commercial banks in Malaysia, using data stretching from 2012 until 2021 and tested using Panel Autoregressive Distributed Lag (ARDL). The general findings suggest that a commercial bank remains stable in the long run with an injection of green financing. The implications of this paper recommend that green finance can be classified as a source of alternative financing tools to mitigate the destabilising impacts of climate change on the bank's operating business and contribute to the stability of the bank.